THE GENESIS OF THE CONFLICTS OF LABOUR MARKET DEVELOPMENT IN A DIGITAL ECONOMY - N. Yu. Kaufman (Publishing House of the State University of Management, 2019)
The labour market from the point of view of its development in the digital environment, where the main focus is the provision of qualified personnel and updating of personnel potential in the sphere of application of digital technologies, has been analyzed. The structure of employment by branches of economic activity has been considered, the regularities, reflecting a role of information and digital technologies, which change a qualitative component of the labour market from both the employee, and the employer, have been revealed. The role of changes in the level of knowledge for the development of professional potential of the employee in the digital economy due to the development of this sphere has been shown.